Senyapan dan Selip Lidah dalam Produksi Ujaran pada Diskusi Kelompok Mahasiswa FIP Universitas Puangrimaggalatung: Kajian Psikolinguistik - Putri Wulandari, Putri Wulandari; Arisa, Arisa; Rahmi, Nur (AIJER: Algazali International Journal Of Educational Research, 2024)
Abstract: The aim of this research is to describe the forms of silence and slips of the tongue in speech production among students at the Faculty of Education, Puangrimaggalatung University. The method used in this research is a qualitative method. In this research, the data collection techniques used were observation, recording, recording and documentation techniques. The results of the research show that there are forms of silence and slips of the tongue in speech production in the discussion process of student groups at the Faculty of Education, Puangrimaggalatung University. The form of silence in speech production in student discussions at the Faculty of Education, Puangrimaggalatung University is divided into two parts, namely silent silence and filled silence. In this study, there were 22 types of speech which were silent silences and 25 speech types which were included in filled silences. Furthermore, the slip of the tongue form is divided into two, namely the slip of the tongue caused by incorrect semantic selection consisting of 12 utterances and the slip of the tongue due to the assembling of 27 utterances when producing utterances in student discussions at the Faculty of Education, Puangrimaggalatung University.